Calculating confidence intervals for percentiles of accelerated life tests with subsampling. Issue 4 (4th July 2019) - Wang, Guodong; Shao, Li; Chen, Honggen; Cui, Qingan; Lv, Shanshan
Abstract: Accelerated life tests usually contain subsampling, which represents a restriction on randomization. The two-stage approach can deal with lifetime data from experiments with subsampling. However, this method did not introduce how to reduce the biases of estimators and compute confidence intervals of low percentiles. In this article, we build the model between percentile and stress factors, and obtain likelihood-based inference on percentile. In addition, we reduce the biases of estimators using an unbiasing factor method. Finally, we illustrate our method through a real example and compare with other methods via simulation study. The simulation results show that our proposed method is better in most cases.